Marketing fortified rice: Effects of aspirational messaging and association with free distribution - Chowdhury, Reajul; Crost, Benjamin; Hoffmann, Vivian (Elsevier, 2022)
Fortification of staple foods is among the most cost-effective public health interventions. In settings where mandatory fortification is not feasible, providing fortified foods through public safety net programs and building private demand can be implemented in parallel to maximize coverage. However, little is known about what marketing messages are most effective at increasing the demand for fortified foods. Further, as governments scale up fortification of foods distributed through safety net programs, understanding the effect of knowledge about this on consumer demand will be important for crafting communication strategies. Drawing on insights from the literature on marketing and consumer behavior, we hypothesize that a message linking fortified rice, an unfamiliar product in this setting, to a known, aspirational product, can increase demand. We test the individual and joint impacts of an aspirational marketing message and information about the public distribution of fortified rice through a framed field experiment eliciting willingness to pay for rice fortified with six micronutrients in Chandpur District, Bangladesh. We find that a message which combines aspirational positioning and information on public distribution increases the proportion of participants willing to pay a premium at least equal to the cost of fortification by 19 percentage points. The results suggest that any negative impact on willingness to pay associated with free distribution is outweighed by the credibility distribution lends to health claims about the product.